Migration and contemporary halieutic societies in the spanish state: strategies and socio-family network (Tempo e Argumento, 2009)
The exodus of the fishing group of Galician origin towards the Atlantic peninsular Spanish south is the result of a provisional emplacement originated in the middle of the 20th century, consolidated by the location of new ports and the discovery of fishing banks with abundant resources in the South Atlantic. In this article we present some guidelines to describe the ethno-historical trajectory of the Galician coast, as well as the migratory and maritime idiosyncrasy of this ethnic group, what leads us to an understanding of the motivations for the displacement of a part of their fleet, coming closer to the social construction of the identity in a fishing culture.
Keywords: maritime ethnology; ethnology; migration and social networks; migration